EVALUATION OF ANAEROBIC LACTACID CAPACITY IN ELITE QWAN KI DO ATHLETES (GYMNASIUM, 2017)
The present research aims to highlight the influence of specific training on anaerobic lactacid capacity in Qwan Ki Do martial art. We started from the hypothesis that the elite athletes from this martial art have good lactacid capacity, that is requested in competition effort. In the study it was included 10 male athletes from Romanian Qwan Ki Do national team. Testing was carried out during the competition period and the results put in evidence a low general level of anaerobic lactacid capacity, suggesting that this energy source occurs less to support the competitive effort.